2016
DOI: 10.1080/19320248.2016.1146195
|View full text |Cite
|
Sign up to set email alerts
|

The Intergenerational Circumstances of Household Food Insecurity and Adversity

Abstract: Household food insecurity is linked with exposure to violence and adversity throughout the life course, suggesting its transfer across generations. Using grounded theory, we analyzed semistructured interviews with 31 mothers reporting household food insecurity where participants described major life events and social relationships. Through the lens of multigenerational interactions, 4 themes emerged: (1) hunger and violence across the generations, (2) disclosure to family and friends, (3) depression and proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 71 publications
3
51
0
Order By: Relevance
“…[17][18][19] Research has demonstrated that adversity may transfer from one generation to the next in the form of abuse/neglect, housing risk, and poor socioemotional health. 16,20,21 Additionally, mothers' history of adversity is associated with depressive symptoms before and after giving birth, and with their infants' maladaptive socioemotional symptoms. 22 However, the mechanisms underlying these patterns are not clear, particularly because there may be reciprocal effects in two-generation relationships, with mothers' reacting to their infants' maladaptive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Research has demonstrated that adversity may transfer from one generation to the next in the form of abuse/neglect, housing risk, and poor socioemotional health. 16,20,21 Additionally, mothers' history of adversity is associated with depressive symptoms before and after giving birth, and with their infants' maladaptive socioemotional symptoms. 22 However, the mechanisms underlying these patterns are not clear, particularly because there may be reciprocal effects in two-generation relationships, with mothers' reacting to their infants' maladaptive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity and its potential consequence of experiencing hunger are two among many social and environmental determinants of child health. A range of these social and environmental factors have been found to cluster together, potentially creating chaotic living conditions for families (9) and reflecting a broader context of family adversity and trauma that can reinforce each other across generations (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should attempt to isolate these effects from the overall associations of SNAP participation and cardiometabolic health. 59, 60 Many prior studies have also found associations between food insecurity and children’s mental health, including greater adversity, 61, 62 more behavioral problems, 6366 worse psychosocial functioning, 67–69 and higher rates of depression and suicidal thoughts. 70 Similarly, environmental factors like the food environment, neighborhood walkability, and exposures to other environment stressors are often correlated with SES and may influence children’s cardiometabolic health.…”
Section: Discussionmentioning
confidence: 98%